1980
DOI: 10.1021/i160076a008
|View full text |Cite
|
Sign up to set email alerts
|

Response of Catalyst Surface Concentrations to Forced Concentration Oscillations in the Gas Phase. The NO, CO, O2 System over Pt-Alumina

Abstract: 80 cm3/(g s) will have a very small (e < 0.025) effect on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Using Monte Carlo simulations they found that this surface model presents the main features of the pure CO-O 2 system, which contains an active phase where the carbon dioxide molecules are produced continuously. After the appearance of this article, an avalanche of other papers concerning the reaction catalytic surfaces also have appeared in the literature [4][5][6][7][8][9][10][11][12][13][14][15]. In general, these papers are related with the own ZGB model or they are extensions of the same, concerning the various aspects of the experimental observations of these phenomena.…”
Section: Introductionmentioning
confidence: 96%
“…Using Monte Carlo simulations they found that this surface model presents the main features of the pure CO-O 2 system, which contains an active phase where the carbon dioxide molecules are produced continuously. After the appearance of this article, an avalanche of other papers concerning the reaction catalytic surfaces also have appeared in the literature [4][5][6][7][8][9][10][11][12][13][14][15]. In general, these papers are related with the own ZGB model or they are extensions of the same, concerning the various aspects of the experimental observations of these phenomena.…”
Section: Introductionmentioning
confidence: 96%
“…Several experiments show that it is possible to increase the efficiency of catalytic reactions by subjecting the system to periodic external forcing [5,6,7,8,9]. Monte Carlo simulations of the Ziff, Gulari, and Barshad (ZGB) model without desorption [13] indicate that an enhancement of the catalytic activity is observed when the system is perturbed by a periodic force that drives it briefly into the CO poisoned state [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Positive results were in fact reported in a number of studies conducted typically under atmospheric pressure conditions [6][7][8][9][10]. Under these conditions mass and heat transfer plays a dominant role contrary to the low pressure ( p < 10 −3 mbar) single crystal experiments in which periodic forcing was also investigated.…”
Section: Introductionmentioning
confidence: 90%
“…Non-stationary reaction conditions may im-prove the yield and selectivity of reactions or reduce energy consumption as compared to stationary conditions [4][5][6]. oxidation of CO and unburned hydrocarbons as well as NO reduction [6][7][8][9][10]. In heterogeneous catalysis experimental studies with periodic forcing focused on the reactions of the automotive catalytic converter, i.e.…”
Section: Introductionmentioning
confidence: 99%